The Investigation of Gastroesophageal Reflux in Children with Portal Hypertention - Alim, Altan; Eliçevik, Mehmet; Alim, Elmas Reyhan; Önal, Zerrin; Can, Günay; Şenyüz, Osman Faruk (Cerrahpaşa Medical Journal, 2021)
Objective: To investigate the effect of the portal hypertension on gastroesophageal reflux disease in childhood. Methods: A total of 30 patients with portal hypertension were included in the study. The patients were divided into 3 main groups; Group I: patients without sclerotherapy, Group II: patients on the endoscopic sclerotherapy program, Group III: patients who had surgical devascularization. Gastroesophageal reflux symptoms, endoscopic findings of esophagitis and 24-hour pH monitorization were noted. The Fisher exact test was used for statistical analysis. Results: This study showed that the incidence of gastroesophageal reflux was significantly higher in all these three groups than in healthy people. There were no significant differences among the groups on the basis of the symptoms. In the endoscopic examination, reflux was found higher in groups I and III than in group II, whereas, in the 24-hour pH monitorization, no significant differences were seen among the groups. Conclusion: Portal hypertensive patients have higher incidence of gastroesophageal reflux than healthy population. Clinical signs and symptoms, endoscopic examination and pH monitorization should all be evaluated together. Because of the increased reflux ratio, all children with portal hypertension should be treated. Cite this article as: Alim A, Eliçevik M, Alim ER, Önal Z, Can G, Şenyüz OF. The Investigation of Gastroesophageal Reflux in Children with Portal Hypertention. Cerrahpaşa Med J 2021; 45(1): 28-32.